2011
DOI: 10.1590/s0066-782x2011005000002
|View full text |Cite
|
Sign up to set email alerts
|

Suporte ventilatório na capacidade funcional de pacientes com insuficiência cardíaca: estudo piloto

Abstract: Background: Heart failure (HF) is an important public health problem, of which main clinical symptoms are dyspnea and fatigue. Noninvasive ventilatory support has been used as adjuvant therapy in cardiac rehabilitation in order to improve the functional capacity of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 21 publications
(16 reference statements)
0
42
1
5
Order By: Relevance
“…Two of the four studies selected4 , 5 , 20 , 21 were indexed in the PEDro Scale4 , 21 and had a score available in the database. Two studies5 , 20 were scored after reading the papers fully and consensus among the three assessors was achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the four studies selected4 , 5 , 20 , 21 were indexed in the PEDro Scale4 , 21 and had a score available in the database. Two studies5 , 20 were scored after reading the papers fully and consensus among the three assessors was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal ventilatory responses, which are common in patients with HF4, combine with peripheral muscle dysfunction to reduce the patients' ability to perform daily life tasks and impair their quality of life4 , 5, directly affecting their ability to perform physical exercise. Although studies have shown direct benefits from regular physical training in patients with HF by promoting a gradual improvement in tolerance to effort6, increased maximal oxygen consumption (VO 2 )7, and increased oxidative capacity of the skeletal muscles8, the blood flow to the respiratory muscles tends to rise significantly during exercise training because of the redistribution of blood flow from the locomotor muscles9.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that elderly individuals with low education have greater exposure to risk factors related to cardiovascular disease as a result of the peculiarities of its demographic and epidemiological profile (CARNELOSSO et al, 2010;FARIA et al, 2015;IMA et al, 2011). It's emphasized the importance of special attention to the health care of the targeted population with low social instruction and school education, either by recruitment of specialized health professionals and / or specific health policies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the literature highlights serious deficits on the PHS of patients with heart failure NYHA IV, since it has negative impact on the functional capacity, exacerbated clinical symptoms and reduction of social life (GUIMARÃES; GARDENGHI; SILVA, 2015;IMA et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of non-invasive ventilatory support (NIV) can improve tolerance to the exercise, as it improves the cardiorespiratory response during the exercise (10). The usage of this therapeutic modality is indicated in acute respiratory failure, chronic obstructive pulmonary disease (COPD), acute pulmonary edema, congestive heart failure (CHF) (11), among other situations.…”
Section: Introductionmentioning
confidence: 99%